Pengaruh Harga dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Fesyen Muslim di Tokopedia Salam - Nur Huri Mustofa; Putri Pratiwi Sutrisna (Institut Agama Islam K.H. Sufyan Tsauri, 2023)
Tokopedia Salam is the first marketplace in Indonesia that specifically sells halal products, Muslim fashion and services related to Muslims. This feature was released by Tokopedia since 2019 with the aim of making it easier for Muslims to fulfill their daily needs without fear that the products or services purchased contain ingredients that are forbidden in Islam. This study aims to determine the effect of Price and Ease of Use on Muslim Fashion Purchase Decisions at Tokopedia Salam. The type of research used is quantitative research. Data collection was carried out through questionnaires distributed to Tokopedia Salam consumers in Central Java using a purposive sampling technique. Data analysis of this study includes instrument tests, namely validity and reliability tests, classical assumption tests, namely normality tests, multicollinearity and heteroscedasticity, and statistical tests, namely the validity test of influence (t), model suitability test (f) and determination coefficient test (R2) which are processed using SPSS. The results of the study indicate that based on the t-test, price and ease of use have a significant positive effect on purchasing decisions, price and ease of use also have a joint effect on purchasing decisions.